2013
DOI: 10.1103/physreve.87.013009
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motion of a droplet induced by interfacial tension

Abstract: Spontaneous rotation of a droplet induced by the Marangoni flow is analyzed in a two-dimensional system. The droplet with the small particle which supplies a surfactant at the interface is considered. We calculated flow field around the droplet using the Stokes equation and found that advective nonlinearity breaks symmetry for rotation. Theoretical calculation indicates that the droplet spontaneously rotates when the radius of the droplet is an appropriate size. The theoretical results were validated through c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
(16 reference statements)
0
28
0
Order By: Relevance
“…On the other hand, there are also asymmetrical objects moving in a homogeneous field, for example, an asymmetrical camphor fragment, an ethanol boat, an oil droplet with a solid particle, and a gel boat with carbon nanotubes . These objects have lower surface tension in water on one side than the other, thereby inducing a driving force.…”
Section: Self‐propelled Objects Driven By Interfacial Chemical Energymentioning
confidence: 99%
“…On the other hand, there are also asymmetrical objects moving in a homogeneous field, for example, an asymmetrical camphor fragment, an ethanol boat, an oil droplet with a solid particle, and a gel boat with carbon nanotubes . These objects have lower surface tension in water on one side than the other, thereby inducing a driving force.…”
Section: Self‐propelled Objects Driven By Interfacial Chemical Energymentioning
confidence: 99%
“…Liquid crystals enable us to extract a specific mode of motion by controlling the symmetry inside the droplets [25][26][27][28], where straight, curvilinear, and spiral motions, and their transitions, have been demonstrated. As a simpler case, spontaneous symmetry breaking of the motion of a swimming droplet in a two-dimensional (2D) system was investigated experimentally [29,30] and theoretically [31], which identified the straight-to-curvilinear motion transition. Recent experimental studies reported that an increase of the external surfactant concentration or the viscosity of the swimming medium causes the curvilinear motion of a swimming spherical droplet [22,23].…”
mentioning
confidence: 99%
“…This boundary condition mimics the experimental results with the symmetric distributions of temperature and flow. Asymmetric convection due to higher order terms in the Marangoni instability would become important in a higher laser power condition [36].…”
Section: A Numerical Methodsmentioning
confidence: 99%
“…We may also expect the nonlinear terms can cause unique effect on the convective motion inside the droplet, under the breaststroke-like convection. In some of the past studies, a bifurcation from vectorial motion into rotational motion has been observed when the driving force of the propelled motion is increased [26,36]. In the rotational motion caused under the condition with a larger driving force, the breaststroke-like convection breaks the symmetry to be an asymmetrical rolling pair, which causes the steering on the droplet.…”
Section: B Comparison Between the Experiments And The Numerical Simulationsmentioning
confidence: 98%